2014
DOI: 10.1080/02185385.2014.885212
|View full text |Cite
|
Sign up to set email alerts
|

Consumer measures and research co-production: a pilot study evaluating the recovery orientation of a mental health program collaboration

Abstract: A clinical service and a community-managed service have collaborated to deliver a service supporting people with severe and enduring mental illness and complex needs. This study aims to evaluate the recovery-orientation of the service by means of a consumer-led program evaluation utilising validated measures and qualitative interviews. The Recovery Self-Assessment (RSA) and the Recovery Enhancing Environment measure (REE) indicated that the things done well included goal setting and monitoring, practical assis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 15 publications
(10 reference statements)
0
14
0
2
Order By: Relevance
“…Others involve more complex manualised pro-recovery interventions or modules, such as the REFOCUS model, IMR program, and WRAP, which also emphasises peer support in the development of individual recovery plans [65]. Strengths-based case management models supporting consumer directed care have also been implemented in both acute and community MH settings [69, 71], focusing on personal strengths and goals rather than deficits, and integrating a variety of EBIs. While all approaches support recovery, few provide an overarching framework and service-wide model for MH care provision.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others involve more complex manualised pro-recovery interventions or modules, such as the REFOCUS model, IMR program, and WRAP, which also emphasises peer support in the development of individual recovery plans [65]. Strengths-based case management models supporting consumer directed care have also been implemented in both acute and community MH settings [69, 71], focusing on personal strengths and goals rather than deficits, and integrating a variety of EBIs. While all approaches support recovery, few provide an overarching framework and service-wide model for MH care provision.…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing literature on the selection of strategies and measures for assessing recovery [4, 9294], recovery-oriented practice [65, 74, 95] and the recovery-orientation of services [71, 92, 96, 97]. In choosing a particular set of tools, it may be useful to cover a representative range of recovery domains or processes, such as the CHIME spectrum described earlier [38, 64] or the ‘broad superordinate recovery dimensions’ suggested by Whitley and Drake [98] (i.e., clinical, existential, functional, physical, and social dimensions of recovery).…”
Section: Introductionmentioning
confidence: 99%
“…Health professionals can use C–FIS–HP as a clinical tool to assess the comfort level of patients in a helping relationship, as well as use this information to develop culturally sensitive therapeutic interventions and treatment plans. Moreover, understanding the helping relationship can be an excellent method for health professionals to reflect on their communication skills [ 55 ] and develop in-service training and educational programs to enhance therapeutic relationships and the quality of their services [ 6 ]. We believe that further use of this instrument will allow additional sophisticated data analysis techniques for further validation and generalizability of C–FIS–HP in a variety of settings.…”
Section: Discussionmentioning
confidence: 99%
“…The helping process depends on an open, honest, caring, and empathic relationship between patients and their health professionals [ 1 , 4 ]. Positive helping relationships have significant effect on health outcomes [ 5 ], recovery process [ 6 ], perceived self-care agency [ 7 , 8 ], and medication adherence [ 9 ]. Thus, measuring the helping relationship is important to understand the comfort level of patients in terms of sharing their condition or feelings to health care professionals, who can predict the help-seeking behaviors of the former [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research has found that mental health organisations in Australia have struggled to adopt recovery-oriented practices. [22][23][24] A focus on bureaucratic goals 25,26 over consumer-led goals impede the genuine implementation of recovery-oriented practice into services. The engrained culture of the biomedical model has also been identified as a barrier to implementing recovery-oriented practice.…”
Section: Limitations In Access To Music Therapymentioning
confidence: 99%